Optimizing Secure Communication in Distributed Corporate Networks through PPTP and IPSec VPN Protocols - Angelina Azels, Wilona; Ghozali, Theresia; Siregar, Marsul (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2022)
In today’s industry, company’s activities are scattered in several locations and need internet for communication purposes. However, it will be dangerous if third-parties have access to their information. One of the solutions for securing information exchange is by using Virtual Private Network (VPN). The VPN protocols that will be used are Point-to-Point Tunneling Protocol (PPTP) with the help of Internet Protocol Security (IPSec). These protocols are simulated in VirtualBox that has been previously installed with two Mikrotik routers and two Windows 7 operating systems. The PPTP and IPSec protocols are configured in both routers through Winbox software. For the computers, the IP addresses are configured along with iPerf software for bandwidth analysis. In this VPN simulation, both computers can communicate with each other and have no problem in accessing the internet. In PPTP’s network, the average bandwidth is 1.293 Mbits/sec. Meanwhile, in PPTP with IPSec’s network, the average bandwidth is 0.853 Mbits/sec. There is a slight difference considering that in PPTP, the data packets are only encapsulated. On the other hand, the data packets in IPSec protocol are both encapsulated and encrypted.